2014
DOI: 10.1007/s12031-013-0225-z
|View full text |Cite
|
Sign up to set email alerts
|

Glia Maturation Factor Deficiency Suppresses 1-Methyl-4-Phenylpyridinium-Induced Oxidative Stress in Astrocytes

Abstract: Inflammation is closely intertwined with pathogenesis of Parkinson's disease (PD). Increasing evidence suggests that inhibition of glia-mediated inflammation might represent a promising therapeutic target for PD. Glia maturation factor (GMF), an inflammatory protein, predominantly localized in astrocytes is previously isolated, sequenced and cloned in our laboratory. In the present investigation, we demonstrate that GMF-deficiency in astrocytes upregulates the antioxidant status and limit the extent of lipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 52 publications
4
28
0
Order By: Relevance
“…The reduced release of CCL2 from GMF-KO cells observed in the present study could be due to the inhibition of MAPKs and NF-κB activation as we reported previously (Zaheer et al, 2007). Further, we have also demonstrated that GMF-deficiency in astrocytes upregulates the antioxidant status and limits the extent of lipid peroxidation and production of ROS along with diminished NF-κB-mediated inflammations in MPP + -mediated toxicity (Khan et al, 2014). Our present study shows decreased neurodegeneration with reduced total neurite outgrowth in MPP + treated neuronal cultures obtained from GMF-KO mice brains than from Wt mice brains.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The reduced release of CCL2 from GMF-KO cells observed in the present study could be due to the inhibition of MAPKs and NF-κB activation as we reported previously (Zaheer et al, 2007). Further, we have also demonstrated that GMF-deficiency in astrocytes upregulates the antioxidant status and limits the extent of lipid peroxidation and production of ROS along with diminished NF-κB-mediated inflammations in MPP + -mediated toxicity (Khan et al, 2014). Our present study shows decreased neurodegeneration with reduced total neurite outgrowth in MPP + treated neuronal cultures obtained from GMF-KO mice brains than from Wt mice brains.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, we have used GMF-KO cells in only some experiments to study the effect of the mast cell proteases on brain cells. Our previous studies have demonstrated that GMF activates astrocytes through p38 MAPK and NF-κB signaling pathways (Zaheer et al, 2001; Zaheer et al, 2007) and inhibition of these pathways in GMF-KO glial cells also reduced the inflammatory mediator release in vitro (Khan et al, 2014). The reduced release of CCL2 from GMF-KO cells observed in the present study could be due to the inhibition of MAPKs and NF-κB activation as we reported previously (Zaheer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several novel compounds have been patented for PD treatment based on their iNOS-inhibiting capacities (Zhang et al, 2011;Koppula et al, 2012). Previous studies have demonstrated that PYC has the ability to quench NO radicals and inhibit both iNOS mRNA expression and the iNOS activity (Khan et al, 2014), suggesting its potential application in neurodegenerative disease. In this study, we indeed found that PYC efficiently reduced Rot-induced iNOS/NO.…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic neurotoxin 1- methyl -4- phenyl -1,2,3,6-tetrahydro pyridine (MPTP) administration induces PD in animals. 1-methyl-4-phenyl-pyridinium ion (MPP + ), metabolite of MPTP has been shown to induce oxidative stress, mitochondrial damage, glial activation, inflammatory cytokine/chemokine release and dopaminergic neuronal damage [68]. …”
Section: Introductionmentioning
confidence: 99%